(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2017)
Nowadays surveillance systems have been widely deployed in various places and generate massive amount of video data every day. This raises threats of unauthorized access and potential privacy leakage as the recorded videos usually contain rich identifiable information such as facial biometrics. In order to mitigate the threats, many existing methods perform symmetric encryption on the entire frames in the videos. Unfortunately, these methods could introduce additional computation cost and storage. Moreover, as surveillance systems could be a part of distributed system, the key management is critical and challenging. In this paper, we propose a novel method which incorporates background subtraction technique and RSA encryption algorithm. Rather than encrypting the entire frames of the videos, the proposed detect the regions around moving objects in the frames of video and then perform RSA encryption on the detected regions. And RSA encryption technique has its advantages of key distribution and management. Our experimental results show that the proposed method only involve moderate computation cost and storage.